The effects of water deprivation-induced dehydration on serum acute phase protein concentrations in sheep - DINLER AY, C.; ULUTAS, B. (Journal of the Hellenic Veterinary Medical Society, 2021)
The effects of dehydration on serum acute phase proteins (APPs) concentrations are unknown in sheep. In this study, it was aimed to reveal the effect of dehydration on the blood concentrations of serum amyloid a (SAA), haptoglobin (Hp), ceruloplasmin (Cp) and fibrinogen (Fb) in Kivircik cross-breeds sheep. The animal materials of the study consisted of 20 healthy sheep. They were divided into 4 equal groups: systemic inflammation group (SIG), a single dose of 5 ml Freund’s complete adjuvant (FCA) was administered intramuscularly, drinking water were provided as ad libitum; dehydration group (DEH), a single dose of 5 ml placebo 0.9% NaCl was administered intramuscularly and water was deprived for consecutive 5 days; systemic inflammation+dehydrationgroup (SIG+DEH), a single dose of 5 ml FCA was administered intramuscularly and water was deprived for consecutive 5 days; and the control group (CON), a single dose of 5 ml placebo 0.9% NaCl was administered intramuscularly and drinking water was provided as ad libitum. Also, feed was offered ad libitum throughout the experimental period in all study groups. Blood samples were collected on days 0 (baseline values), 1, 3, 5, and 7 while clinical examinations were performed daily during the study. Significant increases were found in serum Hp, SAA, Cp and plasma Fb concentrations in SIG and SIG+DEH groups. There was a significant increase only in serum Hp concentration over time in the DEH group. In conclusion, this study exhibited that Hp concentration increased as part of an acute phase reaction in water deprivation-induced dehydration in Kivircik cross-breeds sheep.